Place, power and leadership: Insights from mayoral governance and leadership innovation in Bristol, UK. (February 2022) - Hambleton, Robin; Sweeting, David; Oliver, Thom
This article aims to enhance understanding of the role of place in urban leadership by examining the way leadership changed significantly following the introduction of mayoral governance into a UK city. In 2012, 10 cities in England held referendums to decide whether to introduce a directly elected mayor model of leadership. Bristol was the only city to vote in favour of this radical change, and the Bristol Civic Leadership Project, set up before the first mayor was elected in November 2012, was designed to discover what differences the directly elected mayor model might make to the leadership and governance of a city. This article addresses two important questions: (1) Does the institutional design of local governance in a place influence leadership effectiveness? (2) How, if at all, do the leadership styles of the individual elected as mayor affect the quality of place-based governance? The article identifies three main reasons why place is important in public policy – expression of identity, strengthening democracy and enhancing governmental effectiveness – and considers how the leadership innovations in Bristol engage with these three dimensions of place. As well as presenting evidence documenting how bold civic leadership has transformed the governance of a particular British city, the article contributes to leadership studies by exploring the relationships between place, power and leadership.